Communicating with Your Child's Teacher - Suzanna D. Smith (EDIS, 2007)
FCS2252, a 4-page fact sheet by Suzanna D. Smith, provides guidelines for parents to communicate well with their child's teacher. Published by the UF Department of Family Youth and Community Sciences, August 2007.